LITERASI BAGI PARA PETANI PADI LADANG YANG HIDUP DALAM KEMISKINAN - Helena Anggraeni Tjondro Sugianto; Priska Vasantan (Institute of Research and Community Outreach - Petra Christian University, 2021)
In a hamlet in West Kalimantan, there are a lot of farmers who plant field rice live in poverty. Unfortunately, they feel that planting this field rice is a tradition and social identity that cannot be abandoned, so that they seem to be in shackles of poverty with no way out. Therefore, it is necessary to do literacy which can open their eyes to the poverty shackles that have bound them so far, and open their horizons to find other alternatives to increase their income. Apart from that, another important thing is that it is necessary to instill spiritual values that enable them to leave behind the old values they have lived so far, which keeps them in poverty.